Jesus' Sermon on the mount : and his confrontation with the world : an exposition of Matthew 5-10 - Carson, D. A. 1946- (Global Christian Publishers, 1999)
Provides an explanation of the teaching of Jesus in his Sermon on the Mount and the events that follow.